Geometric Transformations in the Plane: Shapes in Motion. - Muccillo de Medeiros, Antonio Paulo; de Medeiros, Lícia Giesta Ferreira (Advances in Social Sciences Research Journal, 2021)
This work intends to analyze the validity of inserting the study of Geometric Transformations in Basic Education. It is based on the analysis, from the historical perspective, of the use of these transformations by man and the development of these concept by mathematicians. It intends to show that this subject can be used as an integrating content between the branches of mathematics in basic education to contextualize teaching of subjects in which students do not easily see a practical application.